Design and Characterisation of pH-Responsive Photosensitiser-Loaded Nano-Transfersomes for Enhanced Photodynamic Therapy - Sooho Yeo; Il Yoon; Woo Kyoung Lee (MDPI AG, 2022)
Photodynamic therapy (PDT) is a non-invasive and tumour-specific therapy. Photosensitizers (PSs) (essential ingredients in PDT) aggregate easily owing to their lipophilic properties. The aim of this study was to synthesise a PS (methyl pheophorbide a, MPa) and design a biocompatible lipid-based nanocarrier to improve its bioavailability and pharmacological effects. MPa-loaded nano-transfersomes were fabricated by sonication. The characteristics of synthesised PS and nano-transfersomes were assessed. The effects of PDT were evaluated by 1,3-diphenylisobenzofuran assay and by measuring photo-cytotoxicity against HeLa and A549 cell lines. The mean particle size and zeta potential for nano-transfersomes ranged from 95.84 to 267.53 nm and −19.53 to −45.08 mV, respectively. Nano-transfersomes exhibited sustained drug release for 48 h in a physiological environment (as against burst release in an acidic environment), which enables its use as a pH-responsive drug release system in PDT with enhanced photodynamic activity and reduced side effects. The formulations showed light cytotoxicity, but no dark toxicity, which meant that light irradiation resulted in anti-cancer effects. Additionally, formulations with the smallest size exhibited photodynamic activity to a larger extent than those with the highest loading capacity or free MPa. These results suggest that our MPa-loaded nano-transfersome system is a promising anti-cancer strategy for PDT.